A Novel Prognostic Model of Early-Stage Lung Adenocarcinoma Integrating Methylation and Immune Biomarkers - Ren, Jin; Yang, Yun; Li, Chuanyin; Xie, Lu; Hu, Ronggui; Qin, Xiong; Zhang, Menghuan (Frontiers in Genetics, 2021)
Lung adenocarcinoma (LUAD) is caused by multiple biological factors. Therefore, it will be more meaningful to study the prognosis from the perspective of omics integration. Given the significance of epigenetic modification and immunity in tumorigenesis and development, we tried to combine aberrant methylation and tumor infiltration CD8 T cell related genes to build a prognostic model, to explore the key biomarkers of early-stage LUAD. On the basis of RNA-seq and methylation microarray data downloaded from the TCGA, differentially expressed genes and aberrant methylated genes were calculated with “DEseq2” and “ChAMP” packages, respectively. A Chi-square test was performed to obtain methylation driver genes. WGCNA was utilized to mine cancer biomarkers related to CD8 T cells. With the consequences of univariate Cox proportional hazards analysis and LASSO COX regression analysis, the prognostic index based on 17 methylation driver genes (ZNF677, FAM83A, TRIM58, CLDN6, NKD1, NFE2L3, FKBP5, ITGA5, ASCL2, SLC24A4, WNT3A, TMEM171, PTPRH, ITPKB, ITGA2, SLC6A17, CCDC81) and 4 CD8 T cell related genes (SPDL1, E2F7, TK1, TYMS) was successfully established, which could make valuable predictions for the survival risk of patients with early-stage LUAD.